SP_0916 Is an Arginine Decarboxylase That Catalyzes the Synthesis of Agmatine, Which Is Critical for Capsule Biosynthesis in Streptococcus pneumoniae - Ayoola, Moses B.; Nakamya, Mary F.; Shack, Leslie A.; Park, Seongbin; Lim, Juhyeon; Lee, Jung Hwa; Ross, Matthew K.; Eoh, Hyungjin; Nanduri, Bindu (Frontiers in Microbiology, 2020)
The global burden of invasive pneumococcal diseases, including pneumonia and sepsis, caused by Streptococcus pneumoniae, a gram-positive bacterial pathogen, remains a major global health risk. The success of pneumococcus as a pathogen can be attributed to its ability to regulate the synthesis of capsular polysaccharide (CPS) during invasive disease. We previously reported that deletion of a putative lysine decarboxylase (ΔSP_0916/cadA) in pneumococcal serotype 4 (TIGR4) results in reduced CPS. SP¬_0916 locus is annotated as either an arginine or a lysine decarboxylase in pneumococcal genomes. In this study, by biochemical characterization of the recombinant SP_0916 enzyme, we determine that arginine is the preferred substrate for this decarboxylase, and that levels of agmatine, the end product of the reaction, is significantly depleted in the arginine decarboxylase (ADC) deficient pneumococci ΔSP_0916/adc. We also show that deletion of the polyamine transporter (potABCD) predicted to import putrescine and spermidine results in reduced CPS while deletion of spermidine synthase (ΔspeE) for the conversion of putrescine to spermidine had no impact on the capsule. Targeted metabolomics identified a correlation between reduced levels of agmatine and loss of capsule in Δadc and ΔpotABCD, while agmatine levels were comparable between the encapsulated TIGR4 and ΔspeE. Exogenous supplementation of agmatine restored CPS in ΔpotABCD and Δadc. These results demonstrate that agmatine is critical for regulating the CPS, a predominant virulence factor in pneumococci.